Investigation of optimum jack-up vessel chartering strategy for offshore wind farm O&M activities. (1st February 2015) - Dalgic, Yalcin; Lazakis, Iraklis; Turan, Osman; Judah, Sol
Abstract: Operating further from shore increases the logistic challenges of offshore wind Operation and Maintenance (O&M) activities. Therefore, available vessels in the market and the variety of benefits & drawbacks of different vessel chartering strategies have to be considered in the O&M planning. In contrast with the prospects, operating expenditure (OPEX) of the offshore wind farms has been increasing, reflecting greater risk for potential investors and current operators. In this context, significant cost reductions can be achieved through optimising the offshore related operations, considering the fact that vessel associated costs dominate the total OPEX of the projects. In this paper, the investigation of optimum chartering strategy for jack-up vessels, which indicates the influence of the chartering strategy, charter period, and the characteristics of the vessels involved in the operations, is introduced. Climate parameters, failure characteristics of turbine components, and the vessel specifications are synthesised in a time domain Monte–Carlo approach. The results can assist operators in developing long-term O&M plans. Through this extensive study, it is concluded that optimum O&M cost can be achieved by selecting optimum chartering strategy for jack-up vessels. In addition, regional collaborations between different offshore wind developers can be an alternative solution to reduce the O&M costs. Highlights: The O&M costs can be decreased by optimising the jack-up chartering strategy. The jack-up vessel charter cost has the largest contribution to the total O&M cost. Utilisation can drop quickly for small sites, when the charter period is increased. Regional collaborations can be the solution towards optimised jack-up vessel cost.